Effective cancer immunotherapy in mice by polyIC-imiquimod complexes and engineered magnetic nanoparticles. (July 2018) - Bocanegra Gondan, Ana Isabel; Ruiz-de-Angulo, Ane; Zabaleta, Aintzane; Gómez Blanco, Nina; Cobaleda-Siles, Beatriz Macarena; García-Granda, María Jesús; Padro, Daniel; Llop, Jordi; Arnaiz, Blanca; Gato, María; Escors, David; Mareque-Rivas, Juan C.
Abstract: Encouraging results are emerging from systems that exploit Toll like receptor (TLR) signaling, nanotechnology, checkpoint inhibition and molecular imaging for cancer immunotherapy. A major remaining challenge is developing effective, durable and tumour-specific immune responses without systemic toxicity. Here, we report a simple and versatile system based on synergistic activation of immune responses and direct cancer cell killing by combined TLR ligation using polyIC as TLR3 and imiquimod (R837) as TLR7 agonist, in combination with the model antigen ovalbumin (OVA) and phospholipid micelles loaded with zinc-doped iron oxide magnetic nanoparticles (MNPs). The combination of TLR agonists triggered a strong innate immune response in the lymph nodes (LNs) without systemic release of pro-inflammatory cytokines. The vaccines showed excellent efficacy against aggressive B16-F10 melanoma cells expressing OVA, which was improved with immune checkpoint abrogation of the immunosuppressive programmed death-ligand 1 (PD-L1) at the level of the cancer cells. By magnetic resonance (MR) and nuclear imaging we could track the vaccine migration from the site of injection to LNs and tumour. Overall, we show this synergistic TLR agonists and their combination with MNPs and immune checkpoint blockade to have considerable potential for preclinical and clinical development of vaccines for cancer immunotherapy. Graphical abstract: Image 1